Mandible infiltration as a clinical signal of extramedullary B-cell acute lymphoblastic leukemia/lymphoma in a child: Report of a rare case - Paulo Victor Mendes Penafort; Lady Paola Aristizabal Arboleda; Sérgio Takashi Kussaba; Izilda Aparecida Cardinalli; Regina Maria Holanda de Mendonça; Márcio Ajudarte Lopes; Pablo Agustin Vargas; Alan Roger Santos-Silva (Oral Oncology Reports)
B-cell lymphoblastic leukemia/lymphoma (B-ALL/LBL) is a type of malignancy involving uncontrolled proliferation of B-precursor lymphoid cells. This case report delineates B-cell lymphoblastic leukemia/lymphoma (B-ALL/LBL) manifesting in the mandible and medullary regions of a 10-year-old female. Clinically, an irregular swelling with bone cortical destruction and weight loss was observed. Histopathological examination revealed proliferation of CD10, CD43, CD79a, PAX-5, TDT, CD99, and FLI-1 positive small round blue cells, with a 49% lymphoblast infiltration in the bone marrow. Chemotherapy was administered, leading to disease control during the 5-year follow-up.